Analisis Transformasi Pembelajaran Agama Islam Dari Surface Learning Ke Deep Learning: (Studi Kasus Kelas X SMA Insan Rabbany) - Selvy Yuspitasari (Yayasan Cerdas Pedia Indonesia, 2025)
This research analyzes the transformation of Islamic Religious Education (PAI) from surface learning to deep learning at SMA Insan Rabbany. Utilizing a qualitative case study, the study explores instructional strategies transition from rote memorization to meaningful, reflective understanding. Data collection involved classroom observations, in-depth interviews, and document analysis. The implementation centers on three fundamental pillars: mindful, meaningful, and joyful learning. Findings indicate that this shift fosters intrinsic motivation and emotional engagement through instruments like the Daily Akhlak Journal and digital personalization via artificial intelligence. Despite challenges such as pedagogical resistance and grade-oriented assessment systems, the transformation successfully bridges the gap between cognitive knowledge and moral practice. Students demonstrate enhanced critical thinking, empathy, and religious moderation. Consequently, deep learning empowers students to internalize Islamic values authentically, preparing them for the complexities of Society 5.0. This model provides a strategic framework for Islamic educational institutions to cultivate spiritually mature and socially responsible learners.